The Impact of the Ethyl Acetate Fraction of Bitter Melon Fruit (Momordica charantia l.) on Insulin Hormone Levels of Diabetic Rats (Rattus norvegicus) Using the Enzyme-Linked Immunosorbent Assay Method - Parawansah; Tien; Amiruddin Eso; Muhammad Junaid Azis; Nuralifah (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2023)
Background: The World Health Organization (WHO) has forecast a rise in the prevalence of diabetes mellitus from 2.8% in 2000 to 4.4% in 2030. Numerous investigations have been undertaken to identify alternate avenues for antidiabetic treatment. Momordica charantia, sometimes referred to as bitter melon, is recognized for its possession of mimic insulin components. The ethanol extracts derived from Momordica charantia have been found to exhibit favorable outcomes in the reduction of blood glucose levels and the stimulation of pancreatic beta cells for the secretion of insulin hormone. Purpose: The purpose of this research is to investigate the impact of bitter melon extract on insulin levels in rats induced with streptozotosin. Method: The present study employed various methodologies to investigate the research question. The present investigation comprised three distinct sets of tests, specifically streptozotosin-induced rats, streptozotosin-induced rats administered with an ethyl acetate fraction of Momordica charantia extract, and non-induced streptozotosin rats. The measurement of insulin levels is conducted using the enzyme-linked immunosorbent assay (ELISA) technique. If the p-value was more than 0.05, an unpaired T-test was employed for data analysis. Result: The research findings indicate that there is no statistically significant distinction in the insulin levels between streptozotosin-induced rats and streptozotosin-induced rats administered with the ethyl acetate fraction of the Momordica charantia extract group (p = 0.081). The insulin levels of streptozotosin-induced rats administered with an ethyl acetate fraction of Momordica charantia extract were found to be statistically similar to those of non-induced streptozotosin rats (p = 0.505). Conclusion: There is no discernible distinction in the insulin levels among streptozotosin-induced rats, streptozotosin-induced rats administered with an ethyl acetate fraction of Momordica charantia extract, and non-induced streptozotosin rats.